1991
DOI: 10.1128/jcm.29.10.2180-2186.1991
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus nuclear antigen 1 linear epitopes that are reactive with immunoglobulin A (IgA) or IgG in sera from nasopharyngeal carcinoma patients or from healthy donors

Abstract: The entire amino acid sequence of the unique region of the EBNA 1 protein was synthesized as a set of 41 20-residue peptides with an overlap of 10 amino acids. The peptides were tested in the enzyme-linked immunosorbent assay for reactivity with immunoglobulin A (IgA) and IgG in sera from 50 patients with nasopharyngeal carcinoma (NPC) as compared with 36 serum samples from healthy Epstein-Barr virus (EBV)-seropositive donors and 5 serum samples from EBV-negative donors. The most immunoreactive peptide for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Interestingly, similar disparities have been directly demonstrated in at least one other EBV-related disorder. Patients with nasopharyngeal carcinoma have been shown to bind different regions of EBNA-1 than normal healthy EBV-positive individuals, including a peptide overlapping slightly with this new infectious mononucleosis epitope [Cheng et al, 1991]. Thus, differential immunological specificity seems to be common to EBVrelated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, similar disparities have been directly demonstrated in at least one other EBV-related disorder. Patients with nasopharyngeal carcinoma have been shown to bind different regions of EBNA-1 than normal healthy EBV-positive individuals, including a peptide overlapping slightly with this new infectious mononucleosis epitope [Cheng et al, 1991]. Thus, differential immunological specificity seems to be common to EBVrelated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the molecular basis of EBV serology has been studied in considerable detail, and immunogenic polypeptides have been defined for distinct EBV syndromes [Foong et al, 1990;Ooka et al, 1991;van Grunsven et al, 1993;Gan et al, 1996;Meij et al, 1999Meij et al, , 2002. For NPC serodiagnosis, a number of candidate molecules have been proposed, which can be produced from natural EBV producer cell lines, from recombinant sources or made by peptide synthesis [Cheng et al, 1991;Joab et al, 1991;Littler et al, 1991;Yip et al, 1994;van Grunsven et al, 1994;Gan et al, 1996;Dardari et al, 2000]. An immunoblot method was employed recently to visualize the overall diversity of NPC-related IgG and IgA responses in Chinese, Indonesian, and Caucasian NPC patients [Fachiroh et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that NPC patients had slightly higher antibody titers to EBV latent proteins, EBNA1, EBNA2, LMP1, and LMP2, than did normal controls [Seigneurin et al, 1987;Rowe et al, 1988;Cheng et al, 1991;Frsch et al, 1993;Xu et al, 2000]. Furthermore, most NPC patients had significantly higher antibody titers to EBV lytic proteins, such as viral capsid antigen (VCA), Zta, DNase, DNA polymerase, and thymidine kinase (TK) [Henle and Henle, 1979;Cheng et al, 1980;Hadar et al, 1986;Littler et al, 1990;Joab et al, 1991;Littler et al, 1991;Andersson et al, 1994].…”
Section: Introductionmentioning
confidence: 99%